2021
DOI: 10.5194/bg-18-3657-2021
|View full text |Cite
|
Sign up to set email alerts
|

Committed and projected future changes in global peatlands – continued transient model simulations since the Last Glacial Maximum

Abstract: Abstract. Peatlands are diverse wetland ecosystems distributed mostly over the northern latitudes and tropics. Globally they store a large portion of the global soil organic carbon and provide important ecosystem services. The future of these systems under continued anthropogenic warming and direct human disturbance has potentially large impacts on atmospheric CO2 and climate. We performed global long-term projections of peatland area and carbon over the next 5000 years using a dynamic global vegetation model … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
19
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 153 publications
4
19
2
Order By: Relevance
“…Our results indicated that TAS and SMN were the primary drivers of soil, litter, and vegetation C pools in NAPR during future periods. This was in line with previous findings (Natali et al 2015, Salmon et al 2016, Schädel et al 2016, Song et al 2018, Müller and Joos 2021. Increasing soil temperature with climate warming leads to deepening soil active layer (Biskaborn et al 2019) and altering the decomposition of soil organic matter (Treat et al 2014).…”
Section: Environmental Factors Associate With Permafrost C Poolssupporting
confidence: 90%
“…Our results indicated that TAS and SMN were the primary drivers of soil, litter, and vegetation C pools in NAPR during future periods. This was in line with previous findings (Natali et al 2015, Salmon et al 2016, Schädel et al 2016, Song et al 2018, Müller and Joos 2021. Increasing soil temperature with climate warming leads to deepening soil active layer (Biskaborn et al 2019) and altering the decomposition of soil organic matter (Treat et al 2014).…”
Section: Environmental Factors Associate With Permafrost C Poolssupporting
confidence: 90%
“…Studies have indicated that peatlands will continue to act as carbon sinks in the next decades under different warming scenarios, but there is a possibility that they become carbon neutral or even a minor carbon source by the end of this century (Chaudhary et al, 2017b(Chaudhary et al, , 2020Gallego-Sala et al, 2018;Qiu et al, 2020). To quantify and understand the overall effects of these rapid changes, various advanced peatland models have been employed, but often these models are forced with limited set of Representative Concentration Pathway (RCP) scenarios (Chaudhary et al, 2020;Müller & Joos, 2021;Qiu et al, 2020). It is a common trend to focus on two-three scenarios in modeling studies in order to obtain end-member estimates.…”
mentioning
confidence: 99%
“…With the development of PEATCLSM Trop , we integrated peat‐specific hydrology modules for natural and drained tropical peatlands into a global LSM for the first time. These modules facilitate the integration of tropical peatland hydrology into Earth system models, possibly resulting in better understanding and projecting current and future global C fluxes (Loisel et al., 2021 ; Müller & Joos, 2021 ). Peatland hydrology and C dynamics are intrinsically linked, including in tropical peatlands where water level dynamics are the main force driving long‐term peat C sequestration (Cobb et al., 2017 ; Couwenberg et al., 2010 ; Dargie et al., 2017 ).…”
Section: Discussionmentioning
confidence: 99%